Extrapulmonary tuberculosis in The Netherlands, an epidemiologic overview, 1993–2022 - Frouke A. Procee; Jizzo R. Bosdriesz; Frank G.J. Cobelens; Maria Prins; Sabine M. Hermans; Anton E. Kunst (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2025)
Background: Extrapulmonary tuberculosis (EPTB) poses significant diagnostic and therapeutic challenges in low-incidence settings like the Netherlands. Despite declining overall tuberculosis (TB) incidence, the proportion of EPTB has risen, especially among migrant populations. This study examines sociodemographic, migration-related, and clinical factors associated with EPTB from 1993 to 2022 to inform TB diagnostics and care. Methods: A retrospective quantitative analysis of 34,048 TB patients reported to the Netherlands Tuberculosis Registry (1993–2022) was conducted. Logistic regression was used to identify associations with EPTB. Temporal trends in EPTB and pulmonary TB (PTB) were evaluated, including stratification by age, country of birth, and duration of residency. Results: Over the study period, the proportion of EPTB rose from 37 % to 50 %. EPTB was more common in women (adjusted odds ratio (aOR) 1.53; 95 % CI 1.45–1.62) and children under 14 years (aOR 2.83; 95 % CI 2.46–3.24). Foreign-born individuals, particularly from India, Somalia, Eritrea, Ethiopia and Pakistan, had higher odds of EPTB compared to Dutch-born individuals (aOR range: 2.33–3.86). EPTB was also associated with HIV infection (aOR 1.73; 95 % CI 1.43–2.11) but inversely related to social risk factors like homelessness and problem substance use. TB was notably frequently diagnosed among individuals residing in the Netherlands for over 10 years, more often EPTB than PTB. Conclusion: The rising proportion of EPTB underscores the need for targeted interventions, particularly for high-risk groups such as women, children and migrants. Enhanced screening, early detection, and preventive strategies, especially for tuberculosis infection (TBI) are critical to reducing EPTB morbidity and mortality.